Animal Politics: Species, Evolution, and Religious Affects. (14th August 2017) - Schaefer, Donovan
Abstract : This article considers four responses to the 2015 volume Religious Affects: Animality, Evolution, and Power and draws out their implications for thinking religion, affect, science, and power.